2001
DOI: 10.1002/hyp.174
|View full text |Cite
|
Sign up to set email alerts
|

Reedbed evapotranspiration rates in England

Abstract: Abstract:Measurements of evapotranspiration from contrasting stands of Phragmites australis [ET(Reed)] were obtained over several years at three sites within England between 1994 and 1998. A comparison with published ET(Reed) values showed the UK rates to be considerably lower than those measured in continental Europe. From the ET(Reed) data monthly crop coefficients [K c (Reed)] have been developed, which when used with Reference Crop Evapotranspiration will enable reedbed water use to be determined. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 7 publications
(7 reference statements)
4
11
2
Order By: Relevance
“…The crop coefficient traditionally recommended for use in estimating reed-bed evapotranspiration in the UK is 1Ð4, and higher results than this have been measured by Fermor et al (2001) on the two smaller of their three sites and by Smid (1975). However, when applying crop coefficients with a grass reference under well-watered conditions, for a vegetation expanse of greater than 50 m, the crop coefficients should not exceed 1Ð3 because there is insufficient energy available without an additional horizontal source (ASCE, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crop coefficient traditionally recommended for use in estimating reed-bed evapotranspiration in the UK is 1Ð4, and higher results than this have been measured by Fermor et al (2001) on the two smaller of their three sites and by Smid (1975). However, when applying crop coefficients with a grass reference under well-watered conditions, for a vegetation expanse of greater than 50 m, the crop coefficients should not exceed 1Ð3 because there is insufficient energy available without an additional horizontal source (ASCE, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The majority have been done using lysimeters (e.g. Fermor et al, 2001) or cut-stem weight change methods, both of which can suffer greatly from enhanced rates of evapotranspiration due to advection and change in transpiration rates due to disturbance. There is often uncertainty that the conditions within the lysimeter are identical to those in the surrounding reedbed (Gilman and Newson, 1983).…”
mentioning
confidence: 99%
“…Also, because the tropical wetlands in the present study had small areas, high length to width ratios (7:1) and were located among dry sugar cane fields, the clothesline and oasis effect (Penman 1963;Linacre 1976) was probably substantial. In addition, Fermor et al (2001) suggested that advection played a more important role for the energy budget in smaller wetlands located in dry areas, and that apphcation of relatively high pan coefficients are justified in such sites. In conclusion, literature suggests that a higher pan coefficient than the recommended of 0.8 by Kadlec & Knight (1996) should be used to transform pan evaporation to wetiand ET, especially for small wetlands located in dry tropical areas.…”
Section: Hydrological Measurementsmentioning
confidence: 97%
“…This approach allowed the restoration planners to compare, directly, the water-regime needs of the arable crops present now with those of restored wetland habitats. To assess vegetation water requirements, the Great Fen work adopted the crop coefficient methodology (Allan et al, 1998), which has lately been increasingly applied to non-crop vegetation (Fermor et al, 2001).…”
Section: Planning Large-scale Wetland Restoration: Is There Enough Wamentioning
confidence: 99%